Insulin injection rotation and Diabetes Mellitus nutritional management education - Indah Rosdiana Narahaubun; Dian Handayani; Heri Kristianto; Heri Kristianto (PAGEPress Publications, 2024)
The management of Diabetes Mellitus (DM) involves implementing a healthy lifestyle and pharmacological interventions through the administration of anti-hyperglycemia drugs. An essential aspect of treating DM patients is insulin administration, which facilitates glucose transportation into cells. This study evaluated the effectiveness of insulin injection rotation and nutritional management education for DM. The literature search utilized the keywords "education,"AND "insulin injection," AND "nutritional management," AND "DM", ranged 2021-2023 Searches were conducted on various databases, including Proquest, NCBI, BMC, ScienceDirect, and other relevant platforms such as Google Scholar. Ten journal articles pertinent to the subject matter were identified in the study. Findings indicate that nutritional education facilitates overall health improvement in individuals with DM, contributing to maintaining average body weight and near-normal blood glucose levels. It also enhances lipid profile and insulin receptor sensitivity while being a preventive measure against acute or chronic complications such as hyperglycemia. It is noted that selecting the appropriate injection site can significantly impact patients' blood glucose levels. While it is recommended to administer injections at consistent locations, repetitive use of the same site may pose risks of side effects, such as lipodystrophy. After conducting a comprehensive review of ten journal articles, it has been concluded that insulin injection rotation and nutritional management education are effective for managing DM.